GLOBALISASI PASAR MODAL DUNIA DAN PENGARUHNYA TERHADAP PASAR MODAL INDONESIA - R Adisetiawan (Universitas Batanghari Jambi, 2017)
This study aims to prove causality, cointegration and the influence of global capital markets with a market capital of Indonesia for the period 2001-2016 with a Granger causality test statistics, cointegration tests and Multiple Regression testing. These results prove that the 99% confidence interval occurred a long term relationship (cointegration) and the significant influence of global market indices with the Indonesia capital market index (CSPI) in Indonesia Stock Exchange (IDX) for the period 2001 to 2016, it indicates that Indonesia's economy has been integrated with global capital markets with varying levels of integration, but is causally there is only one country that has a causal relationship with the Indonesian stock market index (CSPI), the Taiwan stock market index (TWSE).Keywords: Capital Market Integration